Health promoting resources and lifestyle factors among higher education students in healthcare and social work programmes: a survey with a longitudinal multicentre design - Aimée Ekman; Sandra Pennbrant; Anders Sterner; Elenita Forsberg; Lena Hedén; Håkan Nunstedt; Annelie J. Sundler; Margaretha Larsson; Ingrid Larsson; Inger Ahlstrand; Hammar Isabelle Andersson; Qarin Lood; et al. (BMC Public Health)
Abstract Background It has been suggested that the university environment, to improve students’ health status and educational outcomes, should be based on a health promoting approach. More knowledge is needed about health promoting resources and lifestyle factors that may be of value for students in higher education and their future work-life balance. The aim of this study was to explore health-promoting resources, general health and wellbeing, and health promoting lifestyle factors among fourth and final semester students in higher education in healthcare and social work. Methods This longitudinal study is based on self-reported data collected through a web-based questionnaire that included questions about general health, wellbeing, and healthy lifestyle factors and made use of instruments: the Sense of Coherence (SOC) scale, the Salutogenic Health Indicator Scale (SHIS), and five questions from the General Nordic Questionnaire (QPS Nordic). The questionnaire was distributed among students enrolled in seven different healthcare and social work programmes at six universities in Sweden. Data was collected when students were in their fourth (2019/2020) and final (2020/2021) semesters analysed with multiple linear and logistic regressions. Results The survey included responses from students during the fourth (n = 498) and the final (n = 343) semester of higher education programmes in health and social work. Total SOC scores decreased between the fourth semester and the final semester. The prevalence of the health promoting lifestyle factor of physical exercise decreased between the fourth and final semesters. Students in their final semester reported valuing group work more highly than did students in their fourth semester. Despite this, students in both the fourth and the final semester reported high SOC, low levels of good general health and perceived wellbeing, and sleeping problems. Conclusions Students’ report of good general health were associated with wellbeing, high-intensity physical training, and no sleeping problems A high SOC level was associated with good general health, perceived wellbeing, and no sleeping problems. A higher SHIS level was also associated with wellbeing and no sleeping problems. Therefore, we suggest further research focusing on how to prepare students in healthcare and social work during higher education for a future work-life in balance targeting effects on sleep quality.